2017
DOI: 10.1038/nrcardio.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

Physical function and exercise training in older patients with heart failure

Abstract: Heart failure (HF) is a common end point for numerous cardiovascular conditions, including coronary artery disease, valvular disease, and hypertension. HF predominantly affects older individuals (aged ≥70 years), particularly those living in developed countries. The pathophysiological sequelae of HF progression have a substantial negative effect on physical function. Diminished physical function in older patients with HF, which is the result of combined disease-related and age-related effects, has important im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 101 publications
0
34
0
Order By: Relevance
“…A large body of research spanning several decades has shown the safety and efficacy of regular physical activity in improving outcome in heart failure patients regardless of age, sex or ethnicity . Most clinical and experimental studies, however, have evaluated the remodelling of hearts with ischaemic cardiomyopathy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of research spanning several decades has shown the safety and efficacy of regular physical activity in improving outcome in heart failure patients regardless of age, sex or ethnicity . Most clinical and experimental studies, however, have evaluated the remodelling of hearts with ischaemic cardiomyopathy .…”
Section: Discussionmentioning
confidence: 99%
“…The disparate results are probably dependent on the different experimental models. Finally, myocardial fibrosis was evident in AS rats and was not modulated by physical exercise.A large body of research spanning several decades has shown the safety and efficacy of regular physical activity in improving outcome in heart failure patients regardless of age, sex or ethnicity 5,11,54. Most clinical and experimental studies, however, have evaluated the remodelling of hearts with ischaemic cardiomyopathy 55,56.…”
mentioning
confidence: 99%
“…Ageing is accompanied with loss of muscle mass and muscle strength, which results diminished physical function (PF) and debilitating consequences such as fall and mortality in older people (1) .…”
mentioning
confidence: 99%
“…We now know the traditional risk factor such as hypertension, diabetes, smoking, and so on are the major risk factors of CHD [3][4][5][6]. In recent decade, many studies have shown that improving the physical function can help cardiovascular mortality, and improve well-being in older populations [7][8][9]. Walking speed and grip strength were used as surrogate markers of the physical function and represented the main determinants of physical frailty and sarcopenia.…”
Section: Introductionmentioning
confidence: 99%